2009
DOI: 10.1063/1.3092485
|View full text |Cite
|
Sign up to set email alerts
|

Near compensated half-metal in Sr2NiOsO6

Abstract: The electronic and magnetic properties of tetragonal double perovskite Sr(2)NiOsO(6) were studied by use of the density functional theory and including the spin-orbit coupling. Compensated half-metal is found if the spin-orbit coupling is not considered. Spin-orbit coupling induces orbital moments on both Ni and Os, making Sr(2)NiOsO(6) a near compensated half-metal. Ferromagnetic phase is slightly favored over antiferromagnetic phase (by 4 meV). The small energy difference also suggests that both phases are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The DP of A 2 BB ′ O 6 (A= La or Sr) has a rock-salt structure of transition metals BB ′ . 5 In spite of many predictions of CHM in DP-related compounds, 4,[6][7][8][9][10][11][12][13][14] no experimental evidence has been observed. The reasons for this are not yet clear, but some seem to result from antisite disorder on B and B ′ sites.…”
mentioning
confidence: 99%
“…The DP of A 2 BB ′ O 6 (A= La or Sr) has a rock-salt structure of transition metals BB ′ . 5 In spite of many predictions of CHM in DP-related compounds, 4,[6][7][8][9][10][11][12][13][14] no experimental evidence has been observed. The reasons for this are not yet clear, but some seem to result from antisite disorder on B and B ′ sites.…”
mentioning
confidence: 99%
“…In the previous studies, we noticed that various U values are chosen for the two transition metals. For V, they are around 4.0 eV in SrVO 3 [15], 3.5 and 5.0 eV in MnV 2 O 4 [16] as well as larger than 3.3 eV in SrVO 3 and CaVO 3 [17]; while for Os, they are 0.5 eV in Sr 2 CrOsO 6 [4], 2.0 eV in Sr 2 NiOsO 6 [5], 1.5-2.0 eV [20] and 2.7 eV [19] in Ba 2 NaOsO 6 . This means that of our choice of U V = 4.0 eV and U Os = 2.5 eV is acceptable.…”
Section: Lasrvosomentioning
confidence: 95%
“…It was indeed found that they are good candidates for CHM by using the generalized gradient approximation (GGA) method without the inclusion of the SOC effect and electron correlation [6]. However, it has been well established that the electron correlation is important for V [15][16][17], Mo [18], Os [4,5,19,20] and Re [21,22]. In addition, for transition metal atoms, in particular 4d and 5d atoms, the SOC effect is known to be large.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations